A crítica de Sartre ao Ego transcendental na fenomenologia de Husserl - Santos, Adelar Conceição dos (2008)
This dissertation is addressing the criticism of Sartre the notion of transcendental Ego in the phenomenology of Husserl. Within the framework of developing the work of Husserl, the Transcendental Ego can be flagged as a result of the introduction of the concept of epoché, or phenomenological reduction, the "transcendental turn" of phenomenology. The transcendental Ego is both the result of this operation and the principle of formation of any sense of the world. The transcendental phenomenology of Husserl is then Transcendental Idealism. Against this conception, in The Transcendence of the Ego, Sartre presents the argument that I not the content of transcendental consciousness, necessary to ensure its unity and individuality, but a transcendent object. The unity and individuality, for the conscience is guaranteed by intentionality, interpreted as the fundamental character of all consciousness. Through it all conscience is "positional consciousness" (tetic) of its object and "non-positional consciousness" (non-tetic) of itself, so this is the first consciousness non-reflected already consciousness of itself and should be considered independently, since no need to be reflected. However, this way the thesis of Sartre threat inherent tendency to obscure all that it takes conscious reflection, ie it introduces a split between non-reflected and reflection that makes the reflection a fortuitous event. Try during this study provide an answer to this objection to using theoretical tools provided by Sartre in his Phenomenological Ontology. The intentionality serve as a leitmotif of these tests, and that is through their radicalization that Sartre puts in question the very being of consciousness separate from their knowledge. Finally the criticism of Sartre to the transcendental Ego would be an onto-phenomenological approach onto the consciousness.